Foreign direct investment and trade: A bi-directional gravity approach - Monika Harach; Ernesto Rodriguez-Crespo (Kiel Institute for the World Economy (IfW), 2014)
This paper compares the traditional gravity model with a bidirectional approach when multilateral resistance is implemented to analyze the effect of inward foreign direct investment (FDI) on exports. We use cross-sectional HS trade data disaggregated at a 6-digit level in 2010 with controls for HS 2-digit level. Our results show that FDI increases exports only in the in the direction of exporter-importer, and the effect is higher when multilateral resistance is implemented and the effect is different across sections. Our robustness checks show that when FDI is removed, the coefficients and the effect on sectors are similar.
Keywords: C21; F14; F15; F21; 330; FDI; bilateral trade; gravity model; cross-section data; Harmonized System 2-digit code